Peningkatan Pengetahuan Masyarakat KPM-PKH tentang Penyakit Diare dan Kesehatan Lingkungan di Kecamatan Woyla Kabupaten Aceh Barat - Azwar Azwar; Arif Iskandar; Ishalyadi Ishalyadi; Iwan Doa Sempena (Universitas Teuku Umar, 2020)
Diarrheal disease is still one of the main causes of pain and death in the world. Diarrhea has attacked all age groups and severe illness with high mortality obtained in infants and children. Poor environmental conditions are one of the factors increasing the incidence of diarrhea. To overcome environmental problems, one thing that can be done is to increase public awareness and knowledge with indicators of public health through devotion. This community service uses lecture, audio-visual and demonstration methods with very effective results so that it can increase the knowledge and insight of the community in tackling and preventing diarrheal diseases and making people aware of the importance of protecting the environment in order to remain good and healthy.